واقع تنفيذ برامج الشراكة والأنشطة المناسبة التي ينخرط بها المجتمع والأسرة في –العملية التربوية من وجهة نظر الموجهين التربويين- - المقطرن سوزان; صبّوح نسرين (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to study the reality of implementation of the partnership and activities that engage the community and families in the educational process from the standpoint of supervisors in the province of Damascus and work on the implementation thr0ugh parent teacher Advis0ry councils and programs, open day, field visits for pupils in the Community, , in the school of the first episode of primary education in the province. The research and analytical descriptive approach to reach specific goals, and the original community of all supervisors working in the Directorate of Education and Damascus,s( 44) directed and targeted educational been accredited as a sample for research, they applied the resolution as head of res The results showed: that there is no statistically significant differences at the level of significance (a <0.05) between the averages of the views of supervisors about partnership programs and appropriate activities that engage the community and families in the educational process, to create an appropriate school climate in the first cycle of basic education schools in city of Damascus, and work to implement, due to the variable sex and variable experience in educational guidance. هدف البحث إلى دراسة واقع تنفيذ برامج الشراكة والأنشطة المناسبة التي ينخرط بها المجتمع والأسرة في العملية التربوية, من وجهة نظر الموجهين التربويين في محافظة دمشق, والعمل على تنفيذها, من خلال مجالس الآباء والمعلمين والمجالس الاستشارية, اليوم المفتوح, الزيارات الميدانية للتلاميذ في المجتمع, في مدارس الحلقة الأولى من التعليم الأساسي. واعتمد البحث المنهج الوصفي للتوصل إلى الأهداف المحددة, وتكون المجتمع الأصلي من جميع الموجهين التربويين العاملين في مديرية تربية دمشق والبالغ عددهم( 44) موجهاً وموجهة تربوية تم اعتمادهم كعينة للبحث, طبقت الاستبانة عليهم كأداة رئيسة للبحث. دلت النتائج على: أنّه لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة( a< 0.05) بين متوسطات آراء الموجهين التربويين حول واقع تنفيذ برامج الشراكة والأنشطة المناسبة التي ينخرط بها المجتمع والأسرة في العملية التربوية, في مدارس الحلقة الأولى من التعليم الأساسي في مدينة دمشق, , تعزى إلى متغير الجنس ومتغير الخبرة في التوجيه التربوي.